Hydrogenation of Styrene Oxide to 2-Phenylethanol over Nanocrystalline Ni Prepared by Ethylene Glycol Reduction Method - Sunil K. Kanojiya; G. Shukla; S. Sharma; R. Dwivedi; P. Sharma; R. Prasad; M. Satalkar; S. N. Kane (International Journal of Chemical Engineering)
Nanocrystalline nickel prepared by glycol reduction method and characterized by XRD and magnetic measurements has been used as a catalyst for hydrogenation of styrene oxide to 2-phenylethanol. Effect of process variables such as particle size of the catalyst, temperature, and pressure have been optimized to achieve a maximum conversion of 98% of styrene oxide with 99% selectivity towards 2-phenylethanol. The structure of the transition state has been computed employing density functional theory and using Gaussian 09 suite. The enthalpy of reaction (ΔH) and activation energy (Ea) are calculated to be 85.3 kcal·mol−1 and 123.03 kcal·mol−1, respectively. A tentative mechanism for the reaction is proposed according to which atomized hydrogen and styrene oxide react together over the catalyst surface to produce 2-phenylethanol.